2019
DOI: 10.1177/0145561319840579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Auricular Morphology and Auditory Functions

Abstract: In this study, we aimed to investigate the relationship between the body mass index (BMI) and the morphometric properties of auricula and its acoustic gain characteristics. A total of 45 participants between 18 and 45 years of age were enrolled into the study. Participants' height and weight measurements were recorded for the BMI calculation. On both sides, the morphometric properties of the auricula were measured and recorded. Additionally, the participants were subjected to multidirectional dynamic real ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In our study, measurements were made only in a certain age group, and the lack of age-related comparisons are an important limitation. Besides, body mass index, which is an indicator of body fat level, was associated with soft tissue thickness and positively correlated with ear length and width [11]. Body mass index of the volunteers was not calculated in this study.…”
Section: Limitationsmentioning
confidence: 62%
“…In our study, measurements were made only in a certain age group, and the lack of age-related comparisons are an important limitation. Besides, body mass index, which is an indicator of body fat level, was associated with soft tissue thickness and positively correlated with ear length and width [11]. Body mass index of the volunteers was not calculated in this study.…”
Section: Limitationsmentioning
confidence: 62%
“…Thus, AEMD is one of the precursors for the development of newonset AF. Previous studies demonstrated that AEMD durations were significantly prolonged in patients with AF [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Roshanali al.…”
Section: Discussionmentioning
confidence: 99%
“…All patients demographic and clinical information was recorded, body weight (kg), and height (m) were determined, and body mass index (BMI) (kg/m 2 ) was calculated [12]. All participants systolic and diastolic blood pressure (DBP) were measured.…”
Section: Study Populationmentioning
confidence: 99%